DAMPAK PENGUNGKAPAN TANGGUNG JAWAB SOSIAL TERHADAP PROFITABILITAS PERUSAHAAN - Syahzuni, Barlia Annis; Shienny Florencia (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purposes of this research are to examine (1) the influence of Corporate Social Responsibility disclosure to ROA (2) the influence of Corporate Social Responsibility disclosure to ROE, (3) the influence of Corporate Social Responsibility disclosure to EPS of conventional banks companies listed on the Indonesia Stock Exchange during 2017 – 2019 period. The Corporate Social Responsibility disclosure is measured by CSR Indexes based on Global Reporting Initiative 4th generation (G4). Profitability is measured by ROA, ROE, and EPS. The population used in this study are all companies in the banking industry listed on the Indonesia Stock Exchange in the 2017-2019 period. The sample used is banking companies that disclose Corporate Social Responsibility in 2017 to 2019 using the purposive sampling method. There are 18 companies that meet the criteria as research samples.